Sequential gene regulatory events leading to glucocorticoid-evoked apoptosis of CEM human leukemic cells:interactions of MAPK, MYC and glucocorticoid pathways. (15th August 2018) - Webb, M.S.; Miller, A.L.; Howard, T.L.; Johnson, B.H.; Chumakov, S.; Fofanov, Y.; Nguyen-Vu, T.; Lin, C.Y.; Thompson, E.B.
Abstract: Gene expression responses to glucocorticoid (GC) in the hours preceding onset of apoptosis were compared in three clones of human acute lymphoblastic leukemia CEM cells. Between 2 and 20h, all three clones showed increasing numbers of responding genes. Each clone had many unique responses, but the two responsive clones showed a group of responding genes in common, different from the resistant clone. MYC levels and the balance of activities between the three major groups of MAPKs are known important regulators of glucocorticoid-driven apoptosis in several lymphoid cell systems. Common to the two sensitive clones were changed transcript levels from genes that decrease amounts or activity of anti-apoptotic ERK/MAPK1 and JNK2/MAPK9, or of genes that increase activity of pro-apoptotic p38/MAPK14. Down-regulation of MYC and several MYC-regulated genes relevant to MAPKs also occurred in both sensitive clones. Transcriptomine comparisons revealed probable NOTCH-GC crosstalk in these cells. Graphical abstract: Interactions of GR, MYC and MAPK pathways, from analysis of time course of altered gene regulation in CEM cells. GC (triangle) enters cell and activates GR, which by up- or down-regulating many genes, causes lowered activity and or amounts of antiapoptotic ERK and JNK and enhanced activity of proapoptotic p38. In forward feedback, p38 phosphorylates a specific ser of GR, which further enhances GR activity. GR down-regulates Myc which reduces transcription of JNK and further affects MAPKs via downregulation of various (yellow) other Myc-dependent genes. All arrows indicate direct or indirect regulation. Large right-angle arrows, up or down regulation. .Red indicates increased activity/amount; green, decreased. Highlights: Gene chips were used to follow the timing of responses to Dexamethasone in GR + sensitive or resistant leukemic CEM cell clones. Generally, over the 2–20 h preceding apoptosis, there was cumulative buildup of induced and repressed genes. The sensitive clones shared a subset set of these genes, different from the resistant cell. Myc was down-regulated in the sensitive cells. The MAPK system could be influenced so as to promote apoptosis by a set of the induced and reduced genes in the sensitive cells.